Study Protocol Preparation for Randomized Controlled Trials: Recommendations and Protocol Recording - Ayşe DAĞISTAN AKGÖZ; Zeynep ÖZER (Bezmiâlem Science, 2020)

(untitled)
The World Health Organization (WHO) considers the registration of the study protocol as the publication of an internationally recognized set of information on the design, conduct, and management of clinical trials. Writing a detailed study protocol with all the correct and necessary steps is an important step before starting randomized controlled trials. WHO says that study protocols should be included in a standardized registration system and published on a publicly accessible website. From an ethical point of view, the Helsinki Declaration emphasizes that study protocols should be registered in a public database. In addition, before the implementation process of the RCTs has started, obtaining the registration number (protocol ID) in public databases has become an important necessity for the studies to be published in quality journals. The purpose of this review is to review, consider recommendations and provide guidance for protocol registration during protocol preparation, which is the most important stage of a correctly planned RCT process. It is seen that the culture of planning and adhering to this protocol has not yet become widespread in the researchers in our country as they begin the RCT process, according to the principles of the study protocol preparation. It is thought that the information in this review will guide the researchers at this point.